Rancang Alat Bleaching Tank Pada Proses Pembuatan Kertas Dari Ampas Tebu Dengan Kapasitas 18.000 Ton/Tahun - Silvi Nelly Sya'adah; Ayu Chandra Kartika Fitri (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2021)
The pre-design of the paper mill as it will be designed is based on a capacity of 18,000 tons/year, with bagasse mainly containing cellulose. The location of this factory was established in Sukosari Village, Djatiroto District, Lumajang Regency, East Java. The factory's location was chosen to be close to the source of raw materials, namely bagasse (bagasse) which is the waste of a sugar factory in the Lumajang area, including PG Jatiroto. Paper mills work for 300 days a year based on the production process every day. The method used in papermaking is one of the soda processes based on several stages, including the pre-treatment stage, cooking as can be used to remove lignin using 10% NaOH solution at a temperature of 170°C and a pressure of 8 atm. Next in the bleaching stage is the bleaching process with the help of H2O2 at a temperature of 70°C and a pressure of 1 atm, and the last stage is post-treatment which can form sheets of paper. The primary tool used is a bleaching tank for the bleaching process with a capacity of 5,908,5096 kg/hour, and after calculations, the bleaching tank is obtained with SA 240 Grade M type 316 stainless steel construction. A vertical stirred paddle vessel with a head and bottom in the form of a standard dished, type Double Welded Butt Joint welding, and a corrosion factor of 1/16 inc. The bleaching tank has a height of 3.7198 m, a diameter of 1.8962 m, a shell height of 2.9718, a design pressure of 17.606, and a residence time of 70 minutes.